Evaluación de la actividad antibacteriana, in vitro, del extracto etanólico de las vainas de Caesalpinia Spinosa (tara) en cepas de Staphylococcus Aureus - Fernandez Perez, Nelida Lilebet (Universidad Privada de Huancayo Franklin Roosevelt, 2022)
Determinar la actividad antibacteriana, in vitro, del extracto etanólico de Caesalpinia spinosa (tara) en cepas de Staphylococcus aureus. El tipo de investigación realizada fue aplicada prospectiva con un diseño con dos grupos de control (negativo y positivo). La población correspondió a Caesalpinia Spinosa “Tara” recolectada en el distrito de Churin, departamento de Lima, Perú. Para el estudio se utilizaron 500 gr. De vainas Se encontró que el extracto etanólico al 25%, 50%, no posee actividad antibacteriana, Mientras que 100% A dichas concentración presentó mejores resultados en la medición de los halos de inhibición comparando con la claritromicina concluimos que el extracto etanólico de las vainas de caesalpinia espinosa tiene efecto antibacteriano casi similar a la claritromicina.

To determine the in vitro antibacterial activity of the ethanolic extract of Caesalpinia spinosa (tara) on Staphylococcus aureus strains. The type of research carried out was prospective applied with a design with two control groups (negative and positive). The population corresponded to Caesalpinia Spinosa "Tara" collected in the district of Churin, department of Lima, Peru. It was found that the ethanolic extract at 25% and 50% had no antibacterial activity, while 100% at these concentrations showed better results in the measurement of inhibition halos compared to clarithromycin. We conclude that the ethanolic extract of caesalpinia spinosa pods has an antibacterial effect almost similar to clarithromycin.
Evaluation of the antibacterial activity, in vitro, of the ethanol extract of the pods of Caesalpinia Spinosa (Tara) in Strains Of Staphylococcus Aureus
Keywords: Caesalpinia Spinosa; Staphylococcus Aureus; Extracto etanolico; http://purl.org/pe-repo/ocde/ford#3.01.05